In vitro and in vivo evaluation of graphene/titanium dioxide composites for synthetic Keratoprosthesis skirts - Goh, Gwendoline Tze Wei (2018)
The design of an artificial cornea skirt requires consideration of its mechanical strength, corrosion resistance as well as biocompatibility in the ocular environment. Herein we report the first study on graphene/titania (TiO2) ceramics for this application. We used graphene oxide (GO, 100–400 nm) and large crystal graphene oxide (LCGO, 20–40 μm) as graphene precursors, and the composites were prepared by an advanced sintering technique, spark plasma sintering. Their mechanical properties were investigated, and corrosion resistance was studied in artificial tear fluid through anodic polarization and long-term incubation. In vitro safety and biocompatibility was assessed using primary human corneal stromal fibroblast culture, and the implantation of fabricated TiO2/GO or TiO2/LCGO composite on rabbit cornea model was performed and in vivo stability and corneal tissue responses were evaluated. Our results showed that that TiO2/LCGO mixed at 1% wt/wt was a preferable graphene precursor which resulted in mechanically stronger and chemically stable compound when compared to other mixture percentages and TiO2/GO(1%). Furthermore, we demonstrated that graphene/TiO2 hybrid possessed outstanding biocompatibility with corneal stromal fibroblasts and induced stronger tissue adherence when transplanted into rabbit stroma. This suggested that graphene/TiO2 hybrid could be a highly promising candidate material to use in keratoprosthesis skirt, a major component of artificial keratoprosthesis for the treatment of end-stage corneal blindness worldwide.